Impact of reporting foreign exchange gains on capital market reactions (an empirical study of manufacturing companies listed on the Jakarta stock exchange in 2003-2004) - Indah Istriani (Digital Business: Tren Bisnis Masa Depan, 2021)
The purpose of this study is to test empirically the impact of reporting foreign exchange gains on market reactions. The results of previous studies state that there is a correlation between the exchange rate (exchange rate) and stock prices. Based on these studies, researchers are motivated to conduct this research. This study uses Abnormal Return and Trading Volume Activity as a proxy for market reaction and uses 41 manufacturing companies listed on the Jakarta Stock Exchange in 2003-2004 as samples. The sample selection used purposive sampling method. Market reaction to the reporting of foreign exchange gains is tested using the event study methodology. Researchers make corrections to beta to reduce the influence of bias on the Jakarta Stock Exchange. Correction for beta uses the Fowler and Rorke (1983) method with four leads and four legs. The statistical method used to test the hypothesis is multiple regression analysis. Before carrying out multiple regression analysis, a classical assumption test was first performed to obtain an unbiased and efficient estimator or Best Linear Unbias Estimator (BLUE). The results of this study indicate that there is a significant market reaction around the publication date of the financial statements reporting foreign exchange gains by the company. This study shows that the reporting of foreign exchange gains has a significant effect on market reactions as measured by Cummulative Abnormal Return. However, there is no significant effect from reporting foreign exchange gain on Trading Volume Activity.